Satisfaction towards fast food restaurant services: a case study of KFC in Bandar Hilir / Asnida Mohd Zakaria , Norfatira Kudus and Nurul Fisha Musa - Mohd Zakaria, Asnida; Kudus, Norfatira; Musa, Nurul Fisha (Faculty of Hotel and Tourism Management, 2015)
Customer satisfaction has become an important issues for fast food restaurants. The purpose of this research is to study the customer's satisfaction towards the food quality, service quality, perceived value and customer satisfaction towards Kentucky Fried Chicken (KFC) in Bandar Hilir, Melaka. The research methodology used in this study was convenient sampling technique where 370 respondents were where chosen to answer the questionnaire.Besides on findings and data analysis, most of the customers are satisfied with the service quality at the KFC in Bandar Hilir, Melaka, these have been concluded in a DINESERV. The factors that influence customer satisfaction are tangibles, assurance, reliability, responsiveness and empathy. After that, the second most of the customers are satisfied with the perceived value or the price of the KFC itself. This has been found in data analysis. Other than that, the researcher is also able to give some recommendations and suggestions on how to improve and increase customer satisfaction of the customer after the analysis, findings and interpretation.This study will identify their weaknesses in order to achieve customer's satisfaction. The researcher hopes that this study could help this organization to overcome their problem so that they can maintain their established named as the one of the well known fast food in Bandar Hilir, Melaka also in Malaysia.